LEVELS OF KNOWLEDGE OF POSYANDU CADRES WITH EARLY STUNTING DETECTION ABILITY IN SLATENG VILLAGE, JEMBER DISTRICT - Umi Sokowati Sokowati; Lailil Fatkuriyah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Stunting is one of the most common nutritional problems experienced by toddlers in the world today. Stunting can be caused one of them by the lack of knowledge level of parents and posyandu cadres who have the duty to provide services to mothers and children. The bad result of stunting is the disruption of cognitive, motor and verbal development in children who are not optimal. The purpose of this study was to determine the relationship between the knowledge level of posyandu cadres and the ability to detect early stunting. This research method is quantitative with a cross-sectional approach technique with 30 samples with a total sampling technique using measuring instruments used on the knowledge variable of posyandu cadres using a posyandu cadre knowledge questionnaire about early detection of stunting and the variable ability of early detection of stunting using a checklist sheet of cadres ability in early detection of stunting. . The results of the analysis using the spearman rank test obtained p value 0.00 0.05 that there is a relationship between the knowledge level of posyandu cadres and the ability to detect early stunting in Slateng Village, Jember Regency. The level of knowledge of posyandu cadres about stunting has an effect on increasing the ability to detect early stunting, therefore it is necessary to collaborate with the puskesmas to design an activity program with the aim of increasing the ability and independence of cadres in carrying out their roles and functions in community health development.